A cellular triad for linking cardiac niche to regeneration - Xiaokai Ma; Junjie Hou; Jing-Wei Xiong (Cell Regeneration)
Abstract Cardiovascular disease is the leading cause of mortality with very limited therapeutic interventions, thus holding great hope for cardiac regenerative medicine. A recent work from Martin’s laboratory reports their identification of a fetal-like cardiomyocyte progenitor, adult cardiomyocyte type 2 (aCM2), and its potential interactions with C3+ cardiac fibroblasts and C3ar1+ macrophages to form a regenerative cellular triad, which is only present in the regenerative heart models, YAP5SA-expressing adult hearts and neonatal hearts. The complement signaling is essential for cellular interactions in this regenerative triad. This Highlight summarizes these major findings and provides brief perspectives on the impact of this regenerative niche during cardiac regeneration in the future.